2021
DOI: 10.3390/ijerph19010089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Attentional Focus on Muscular Endurance: A Meta-Analysis

Abstract: Several studies explored the effects of attentional focus on resistance exercise, but their analysed outcomes most commonly involved surface electromyography variables. Therefore, the effects of attentional focus on resistance exercise performance remain unclear. The aim of this review was to perform a meta-analysis examining the acute effects of external focus vs. internal focus vs. control on muscular endurance. Five databases were searched to find relevant studies. The data were pooled in a random-effects m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…The Flanker task which was used in the current study measures executive function that enable an individual to focus attention [ 36 ]. Since attentional focus is already reported to moderate acute muscle performance [ 32 , 33 ], decrements in bench press endurance performance during high and moderate hypoxia may be associated with equivalent impairment in cognitive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Flanker task which was used in the current study measures executive function that enable an individual to focus attention [ 36 ]. Since attentional focus is already reported to moderate acute muscle performance [ 32 , 33 ], decrements in bench press endurance performance during high and moderate hypoxia may be associated with equivalent impairment in cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…As the severity of hypoxia increases, the level of deoxygenation increases. Moreover, two recent meta-analyses reported that attention, a parameter of complex cognitive processes, moderates acute muscular endurance [ 32 ] and strength [ 33 ] performance. However, currently there are no studies that have investigated CF before and after resistance exercise during hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some scientific evidence reported improved neuromuscular efficiency during an external focus of attention compared to internal focus in such tasks as isokinetic elbow flexions [ 31 ], isometric force production tasks [ 32 ] or isometric plantar-flexion [ 33 ]. Also, it was proved that an external focus of attention enhanced muscular endurance compared with an internal focus [ 34 ]. Hatami et al [ 35 ] found that in no instruction situations, shoulder muscle activity did not change significantly as compared with the external focus of attention situation during forehand stroke in table tennis.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of attention focus on muscle strength [18], muscular endurance [19], and tasks requiring accuracy have been reported. Several studies have reported shortterm gains in muscle strength when external focus is used.…”
Section: The Effects Of Attention Focus On Muscle Strength and Endurancementioning
confidence: 99%